2018
DOI: 10.2209/tdcpublication.2016-0042
|View full text |Cite
|
Sign up to set email alerts
|

Condition-specific Quality of Life Assessment at Each Stage of Class III Surgical Orthodontic Treatment —A Prospective Study—

Abstract: Surgical orthodontic treatment has been reported to improve oral health-related quality of life (OHRQL). Such treatment comprises three stages: pre-surgical orthodontic treatment; orthognathic surgery; and post-surgical orthodontic treatment. Most studies have focused on change in OHRQL between before and after surgery. However, it is also necessary to evaluate OHRQL at the pre-surgical orthodontic treatment stage, as it may be negatively affected by dental decompensation compared with at pre-treatment. The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
1
18
0
1
Order By: Relevance
“…In terms of OQLQ questionnaire, the scores of all domains increased at T 1 , this difference was statistically significant for facial aesthetics ( P < 0.01) and oral function ( P < 0.05), but decreased significantly across all domains after post-surgical orthodontic treatment. Previous studies have also reported this unexpected observation [22, 34, 35], suggesting that quality of life in patients with Class III malocclusion may be worsened during the treatment. The cause of this phenomenon may be due to the psychosocial disadvantages [36] and the worsening of malocclusion [3739] during pre-surgical orthodontic treatment.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…In terms of OQLQ questionnaire, the scores of all domains increased at T 1 , this difference was statistically significant for facial aesthetics ( P < 0.01) and oral function ( P < 0.05), but decreased significantly across all domains after post-surgical orthodontic treatment. Previous studies have also reported this unexpected observation [22, 34, 35], suggesting that quality of life in patients with Class III malocclusion may be worsened during the treatment. The cause of this phenomenon may be due to the psychosocial disadvantages [36] and the worsening of malocclusion [3739] during pre-surgical orthodontic treatment.…”
Section: Discussionmentioning
confidence: 54%
“…However, Lee et al reported the improvements of all domains except for awareness of dentofacial aesthetics at postoperative 6 months [26]. Choi et al [10] and Tachiki et al [35] also observed the same findings at the same stage. Cultural and social differences are one of the possible reasons for these results.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…[13][14][15]17,18 The preoperative deterioration of patients' OHRQoL treated with COST was realized in different studies and could be attributed to the worsening of malocclusion and psychological disadvantages. 20 Dental decompensation in the presurgical phase had a negative impact on facial esthetics, and most patients considered it as the most stressful period during treatment. 21 Therefore, dental professionals should be aware of the harmful changes during presurgical orthodontic treatment and inform their patients what to expect and, if necessary, help them to overcome the negative effects.…”
Section: Summary Of Evidencementioning
confidence: 99%
“…At the same time-point, the patients in CTM group were just at the beginning of presurgical orthodontics and had worse facial deformity as a result of dental decompensation by CTM. Anterior crossbite was reported to influence esthetics and mastication function negatively, which contributed to a worse OHRQoL during the presurgical orthodontic stage [48, 49]. It was also reported that 73.6% patients with dentofacial deformities were uncomfortable by their appearance and almost half of them felt functional limitations before surgery, and esthetic and functional domains of QoL were improved after surgery [50].…”
Section: Discussionmentioning
confidence: 99%